The Influence of Environment and Job Satisfaction on Employee Performance is Mediated by Employee Commitment at PT X - Wongpy, Joshua Christian; Dewi, Liliana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to analyze the influence of the work environment and job satisfaction on employee performance which is mediated by employee commitment at PT X. The independent variables of this study are work environment (X1) and job satisfaction (X2), the dependent variable of this study is employee performance (Y2), and the mediating variable of this study is employee commitment (Y1). This research is included in quantitative research because the approach used for research proposals, hypothesis determination, and data analysis until writing uses aspects that involve measurement, calculation formulas, and data in numerical form. The sample of this study were employees of PT X who served as middle staff and had worked for more than 6 months. Using the Slovin formula, the required number of samples was determined to be 150 respondents. The data collection method used was distributing questionnaires to respondents via the Google Form. The collected data were analyzed using Smart-PLS version 3 by testing data validity, data reliability, path coefficients, F-Square, R-Square, predictive relevance, and hypothesis testing from this study. The results of this study indicate that the work environment has a significant effect on employee commitment and employee performance, job satisfaction has a significant effect on employee commitment, but has no significant effect on employee performance, and employee commitment has no significant effect on employee performance.